Cryo-EM structures of human ZnT8 in both outward- and inward-facing conformations - Xue, Jing (eLife, 2020)
ZnT8 is a Zn(2+)/H(+) antiporter that belongs to SLC30 family and plays an essential role in regulating Zn(2+) accumulation in the insulin secretory granules of pancreatic β cells. However, the Zn(2+)/H(+) exchange mechanism of ZnT8 remains unclear due to the lack of high-resolution structures. Here, we report the cryo-EM structures of human ZnT8 (HsZnT8) in both outward- and inward-facing conformations. HsZnT8 forms a dimeric structure with four Zn(2+) binding sites within each subunit: a highly conserved primary site in transmembrane domain (TMD) housing the Zn(2+) substrate; an interfacial site between TMD and C-terminal domain (CTD) that modulates the Zn(2+) transport activity of HsZnT8; and two adjacent sites buried in the cytosolic domain and chelated by conserved residues from CTD and the His-Cys-His (HCH) motif from the N-terminal segment of the neighboring subunit. A comparison of the outward- and inward-facing structures reveals that the TMD of each HsZnT8 subunit undergoes a large structural rearrangement, allowing for alternating access to the primary Zn(2+) site during the transport cycle. Collectively, our studies provide the structural insights into the Zn(2+)/H(+) exchange mechanism of HsZnT8.